Benzothiazole Treatment Regulates the Reactive Oxygen Species Metabolism and Phenylpropanoid Pathway of Rosa roxburghii Fruit to Delay Senescence During Low Temperature Storage - Dong, Boyu; Tang, Hongmin; Zhu, Dequan; Yao, Qiuping; Han, Hongqiang; He, Kequn; Ding, Xiaochun (Frontiers in Plant Science, 2021)
Rosa roxburghii fruit were used as research objects to study the effects of different concentrations of benzothiazole (BTH) treatment on quality parameters, reactive oxygen species (ROS) metabolism, and the phenylpropanoid pathway during storage at 4°C for 14days. Results showed that BTH effectively delayed senescence with lower decay incidence, weight loss, and lipid peroxidation level and maintained the quality with higher contents of total soluble solid (TSS) content, titratable acidity (TA) in R. roxburghii fruit. Moreover, BTH increased hydrogen peroxide (H2O2) content, superoxide anion (O2•−) production rate, and the activities and expression of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), glutathione (GSH) reductase (GR), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR), and peroxidase (POD), and the contents of GSH and ascorbic acid (AsA), but reduced the oxidized GSH (GSSG) content. In addition, the activities and gene expression of phenylalanine ammonia lyase (PAL), cinnamate 4-hydroxylase (C4H), and 4-coumarate-CoA ligase (4CL) and the concentrations of flavonoids, total phenols, and lignin were significantly elevated by BTH. These findings imply that BTH can delay senescence and maintain the quality of R. roxburghii fruit by modulating ROS metabolism and the phenylpropanoid pathway under low-temperature conditions.